2022
DOI: 10.4236/jis.2022.134011
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Review of Recent and Landmark Honeypot Research and Surveys

Abstract: The growing interest in Honeypots has resulted in increased research, and consequently, a large number of research surveys and/or reviews. Most Honeypot surveys and/or reviews focus on specific and narrow Honeypot research areas. This study aims at exploring and presenting advances and trends in Honeypot's research and development areas. To this end, a systematic methodology and meta-review analysis were applied to the selection, evaluation, and qualitative examination of the most influential Honeypot surveys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Against this background, one notable trend, or lack thereof, noted previously by Zakaria and Kiah [15] was the lack of innovation stemming from introducing machine learning techniques and other automation methodologies into honeypots and honeynets. While exploring research trends in honeypot and honeynet development, Ikuomenisan and Morgan [3] found the same to be true.…”
Section: Honeypots and Honeynetsmentioning
confidence: 88%
See 1 more Smart Citation
“…Against this background, one notable trend, or lack thereof, noted previously by Zakaria and Kiah [15] was the lack of innovation stemming from introducing machine learning techniques and other automation methodologies into honeypots and honeynets. While exploring research trends in honeypot and honeynet development, Ikuomenisan and Morgan [3] found the same to be true.…”
Section: Honeypots and Honeynetsmentioning
confidence: 88%
“…While early honeypots and honeynets consisted of physical computing systems and networks [17], modern deception implementations are virtualized or containerized and cloud-capable [4]. Additionally, honeypot inspired deceptive systems have evolved in lockstep with emerging technologies such as software-defined networking, tokenized services, or as-a-service models [18,4,3].…”
Section: Honeypots and Honeynetsmentioning
confidence: 99%
“…To the best of our knowledge, we have not found the systematic survey and/or review articles evaluating visualization metrics, methods, and practices relating to attacks and intrusion detection in Honeypot cybersecurity research. Most re-G. Ikuomenisan, Y. Morgan DOI: 10.4236/jis.2022.134012 212 Journal of Information Security lated survey and/or review articles in the field of Honeypot did not follow systematic reviewing and reporting methods [10]. Most related literature surveys,…”
Section: Introductionmentioning
confidence: 99%
“…particularly in fields such as information visualization [2] [11], network anomaly detection [12], data preprocessing, and dimensionality reduction [13] [14] have not presented findings on how visualization methods are used in relation to Honeypot data analysis. Finally, there have been few Honeypot research contributions in the areas of Honeypot data analysis and visualization [10] and this paper hopes to fill this gap.…”
Section: Introductionmentioning
confidence: 99%